2001
DOI: 10.1590/s0100-29452001000300053
|View full text |Cite
|
Sign up to set email alerts
|

OBTENÇÃO E UTILIZAÇÃO DA ENZIMA POLIFENOLOXIDASE EXTRAÍDA DE POLPA DE PINHA (Annona squamosa L.) MADURA NO MELHORAMENTO DO SABOR DO CACAU (Theobroma cacao L.)

Abstract: O presente trabalho teve como objetivo estudar a obtenção e a utilização da enzima polifenoloxidase (PPO) extraída de polpa de pinha madura na redução do teor de compostos polifenólicos com a finalidade de diminuir a adstringência e o amargor das amêndoas de cacau processadas na forma de "nibs". A PPO foi extraída com tampão fosfato de potássio 0,025M (pH 7,5), adicionando sulfato de amônio para a precipitação da enzima. O material em pó obtido foi denominado de enzima parcialmente purificada, sendo que a anál… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
4
0
7
Order By: Relevance
“…Enzymes were extracted in accordance with Lima et al (2001) using 100 g cocoa seed. Pulp was manually separated from the seeds and immersed in 0.02 M potassium phosphate buffer, pH 7.5, with 5% polyethylene glycol and 5 mM ascorbic acid.…”
Section: Extraction Of Pulp Ppomentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymes were extracted in accordance with Lima et al (2001) using 100 g cocoa seed. Pulp was manually separated from the seeds and immersed in 0.02 M potassium phosphate buffer, pH 7.5, with 5% polyethylene glycol and 5 mM ascorbic acid.…”
Section: Extraction Of Pulp Ppomentioning
confidence: 99%
“…Enzymes were extracted in accordance with Lima et al (2001). The seeds were freeze-dried (freeze-dryer Liotop L108) and degreased using petroleum ether as solvent (Yusep et al, 2002).…”
Section: Extraction Of Seed Ppomentioning
confidence: 99%
See 1 more Smart Citation
“…The PPO presence and activity during fermentation and drying of cocoa beans is responsible for the development of flavor precursors, starting during the oxidation phase of fermentation and continuing during drying [7]. PPO activity is also implicated in the reduction of bitterness and astringency of cocoa flavor [8].However, the browning in cocoa is beneficial to some extent as it enhances the quality of the beverages through its forming flavorful products [5].The PPO of cocoa bean has been studied by several groups, showed that it lacked the hydroxylation properties and act only on odiphenols.…”
Section: Introductionmentioning
confidence: 99%
“…O escurecimento enzimático é um fenômeno amplamente observado nesses produtos e induz severas mudanças de cor, sabor e perdas nutricionais (WHITAKER, 1994;LIMA et al, 2001;GARCIA e BARRET, 2005). A polifenoloxidase (E.C.…”
Section: Introductionunclassified